A mathematical model to predict ripening degree of kimchi, a Korean fermented vegetable for meeting consumer preference and controlling shelf life on real time basis. (June 2017) - Jaisan, Chalalai; Lee, Dong Sun
Highlights: Huang's model was adopted to describe acidity change of kimchi with time. Arrhenius equation described temperature dependence of lag time and rate of the acidity increase. A set of comprehensively applicable model parameters was suggested. The model may be used in intelligent packaging for real time indication of kimchi ripening. Abstract: Because microbial activity continues during packaged storage and marketing of kimchi, a Korean lactic acid fermented vegetable, there is a need to indicate the ripening degree represented in acidity on real-time basis, meeting the consumers' preference. Mathematical prediction model of acidity change applicable to dynamic temperature conditions was established using literature data. Huang's model was used to describe it against time providing its lag time and rate of increase for any temperatures of 5–20 °C. The solution of Huang's differential equation using Arrhenius relationship in their temperature dependence could estimate the acidity under dynamic temperature conditions. A set of comprehensively applicable model parameters was formulated from collective data analysis as a basis for generalized application and might be tuned for particular individual case of kimchi . The developed model may be useful to determine consumption time and shelf life under the dynamic product distribution channel by providing real-time indication of ripening state of kimchi .